Pengembangan Sistem Haptic untuk Memegang Objek (Gripper) Dengan Komunikasi Wifi pada Mobile Robot - Muhammad Eraz Zarkasih; Dahnial Syauqy; Wijaya Kurniawan (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Mobile robot with a gripper can help its user to take the remote objects or hold a harmful object. In this case the human perception will be very helpful because humans do not directly interact with the object, hence Haptic can be implemented to simulate the sense of touch. Because mobile robot can be operated remotely by its users then the transmission of the value from the force sensor (Force Sensitive Resistor) and controlling the robot is done wirelessly using WiFi and Android Devices. Based on the implementation, FSR (Force Sensitive Resistor) is used as a sensor to acquire pressure data obtained between the object and gripper. The system use vibration on the Android Device as an indicator of the tightness of the gripper. This system also implements a gripper termination system which automatically terminates gripper on a certain threshold value. From the test results with different objects (Banana, Tomato, Lime) for 10 experiments each for threshold value 50, 100, 150, and 200. To hold the banana, the highest system success is 60% at threshold 100. For Tomato, the highest system success is 100% at 100 and 150 thresholds. For Lime, the highest percentage of system success is 100% at 100, 150 and 200 thresholds. This difference is occurred due to the texture and density in different types of objects.